Roles of Tumor-Associated Macrophages in Tumor Environment and Strategies for Targeting Therapy - Meng-Qi Liu; Jia-Wei Zhang; Jian-Wei Zhu (Pharmaceutical Fronts, 2023)
Tumor-associated macrophages (TAMs) constitute a significant component of the tumor microenvironment. This work reviewed the latest progress in comprehending the function of TAMs and their strategies for cancer therapy. TAMs are highly heterogeneous and plastic and exhibit different functional phenotypes in response to different signal stimuli. The emergence of single-cell technologies allows us to revisit their diversity in cancer. When their pro-inflammatory function is activated, antitumor TAMs support and activate adaptive immune cells to eliminate cancer cells through T cell-mediated killing. In the context of cancer, anti-inflammatory TAMs play a variety of pro-tumor functions, such as releasing cytokines to promote the recruitment of bone marrow cells, promoting tumor angiogenesis, and inhibiting cytotoxic T cell function. The plasticity of TAMs makes them a potential tumor therapeutic target, so finally, we updated strategies for targeting TAMs and the TAM-targeting agents currently being evaluated in clinical trials.